THE USE OF PROJECT-BASED LEARNING IN ENGLISH COURSES FOR NON-ENGLISH MAJOR STUDENTS, VIETNAM NATIONAL UNIVERSITY = NGHIÊN CỨU VỀ VIỆC SỬ DỤNG HỌC TẬP DỰ ÁN TRONG CÁC KHÓA HỌC TIẾNG ANH DÀNH CHO SINH VIÊN KHÔNG CHUYÊN TẠI ĐẠI HỌC QUỐC GIA HÀ NỘI - Phạm, Quang Huy (2020)
The purpose of this study is to explore the perceptions of teachers in Faculty of English, University of Languages and International Studies – Vietnam National University, regarding Project-Based Learning and the current practice of Project-Based Learning in Faculty of English. Survey questionnaires and interviews were carried out on 22 teachers currently teaching general English courses for non-English major students in Faculty of English. The work reveals that the participants possess significant theoretical knowledge despite not being professionally trained for Project-Based Learning and also regard Project-Based Learning as a beneficial approach. Additionally, Project-Based Learning in Faculty of English is only Teacher-Initiated PBL and takes the form of Project exercise or Project component interchangeably. The most challenging factors when implementing Project-Based Learning are identified as Time management and Scaffolding. Future researchers are encouraged to expand the population and compare the perceptions of English major teachers or students to that of non-English major ones in further studies.